An Immersive Journey Through Early Electronic Works of… Latin American Currents - Parra Cancino, Juan; An Immersive Journey Through Early Electronic Works of… Latin American Currents Koetshuis Orpheus Instituut 20 April 2024 (2024)
Tape, Vinyl, and digital, multichannel fixed support pieces, presented in their original formats.
Listening sessions of Early Electronic Music
FRIS
0
Keywords: Music, Thought and Technology